The Influence of Remuneration, Organizational Climate, Mutation, and Leadership on Performance - Pamungkas Prasetyo Aji; Sudarwati; Ida Aryati DPW (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This research aims to determine the influence of remuneration, organizational climate, mutation, and leadership on employee performance. This research method uses a quantitative approach because the data to be processed is ratio data, and the focus of this study is to determine the magnitude of the influence between the variables being examined. This research will be conducted at KPP Madya Surakarta. The planned time for the research is October - November 2024. The population in this study consists of all employees of the Madya Surakarta Tax Service Office, totaling 116 people. Based on the determined sample data, a sample of 26 employees with the position of executor and 40 employees with the position of Account Representative (AR) was obtained. Therefore, the sample in this study consists of 66 people. The dependent variable in this study is the performance of the employees of the Madya Surakarta Tax Service Office. Next, the independent variables in this study are remuneration (X1), organizational climate (X2), mutation (X3), and leadership. (X4). The research results show that remuneration, organizational climate, and mutation have a positive and significant impact on the performance of KPP Madya Surakarta employees. However, leadership does not have a significant impact on the performance of KPP Madya Surakarta employees.